INVESTIGATE THE CARBON FOOTPRINTS OF THREE INTERMEDIATE FLOORING SYSTEMS: CROSS-LAMINATED TIMBER, SOLID CONCRETE, AND HOLLOW-CORE PRECAST CONCRETE - abu qadourah, Jenan; Al-Falahat, Ala’a; Alrwashdeh, Saad (Journal of Applied Engineering Science, 2022)
This paper evaluates and compares the embodied energy and embodied carbon using a Life Cycle Assessment (LCA) approach for three different intermediate floor structures, all of which use prefabricated materials—cross-laminated timber (CLT), precast hollow-core concrete, and solid concrete—to decide which floor construction materials have less environmental impact for use in the construction of a semi-detached house in the UK. The Inventory of Carbon & Energy (ICE) and the Carbon Calculator tool were used to calculate the carbon footprint from “cradle to grave” to determine whether the use of a CLT solution provides improved environmental performance over the traditional concrete solutions. The carbon footprint results indicate that the use of a hollow-core precast concrete floor system emits less carbon than the other two systems, although the concrete requires more fossil fuel input than the timber during the manufacturing process, so based on this, the footprint from cradle to gate for the timber was expected to be the less than that of the concrete. However, the results show the opposite; this is because of the differences in the material quantities needed in each system.